The role of oxidative stress in aortic dissection: a potential therapeutic target - Xu, Shengnan; Han, Xueyu; Wang, Xiukun; Yu, Yi; Qu, Chuan; Liu, Xin; Yang, Bo (Frontiers in Cardiovascular Medicine, 2024)
The incidence of aortic dissection (AD) is steadily increasing, driven by the rising prevalence of chronic conditions such as hypertension and the global aging of the population. Oxidative stress emerges as a pivotal pathophysiological mechanism contributing to the progression of AD. Oxidative stress triggers apoptosis in vascular smooth muscle cells, reshapes the extracellular matrix (ECM), and governs ECM degradation and remodeling, subsequently impacting aortic compliance. Furthermore, oxidative stress not only facilitates the infiltration of macrophages and mononuclear lymphocytes but also disrupts the integral structure and functionality of endothelial cells, thereby inducing endothelial cell dysfunction and furthering the degeneration of the middle layer of the aortic wall. Investigating antioxidants holds promise as a therapeutic avenue for addressing AD.